2005
DOI: 10.1158/0008-5472.can-04-3246
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Replacement of Hypoxia-Inducible Factor-1α by a Hypoxia-Inducible Factor-2α Knock-in Allele Promotes Tumor Growth

Abstract: Hypoxia-inducible factors (HIF) are essential transcriptional regulators that mediate adaptation to hypoxic stress in rapidly growing tissues such as tumors. HIF activity is regulated by hypoxic stabilization of the related HIF-1A and HIF-2A subunits, which are frequently overexpressed in cancer cells. To assess the relative tumor-promoting functions of HIF-1A and HIF-2A directly, we replaced HIF-1A expression with HIF-2A by creating a novel ''knock-in'' allele at the Hif-1a locus through homologous recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 48 publications
5
98
1
Order By: Relevance
“…Although no specific HIF-2a-regulated genes were identified in these studies, other recent reports showed that HIF-2a could indeed up and downregulate a different set of genes than HIF-1a in HEK-293 cells (Wang et al, 2005) and in renal carcinoma cells (Raval et al, 2005). HIF-1a has been shown to activate specifically the glycolytic enzymes PGK and aldolase A, while Oct-4, a transcription factor involved in maintaining pluripotentiality of ES cells, appears to be regulated by HIF-2a but not by HIF-1a (Hu et al, 2003;Covello et al, 2005Covello et al, , 2006.…”
Section: Hif-2a Specifically Activates the Ve-cadherin Gene A Le Brasmentioning
confidence: 66%
“…Although no specific HIF-2a-regulated genes were identified in these studies, other recent reports showed that HIF-2a could indeed up and downregulate a different set of genes than HIF-1a in HEK-293 cells (Wang et al, 2005) and in renal carcinoma cells (Raval et al, 2005). HIF-1a has been shown to activate specifically the glycolytic enzymes PGK and aldolase A, while Oct-4, a transcription factor involved in maintaining pluripotentiality of ES cells, appears to be regulated by HIF-2a but not by HIF-1a (Hu et al, 2003;Covello et al, 2005Covello et al, , 2006.…”
Section: Hif-2a Specifically Activates the Ve-cadherin Gene A Le Brasmentioning
confidence: 66%
“…They have a highly conserved domain architecture, including sites of prolyl and asparaginyl hydroxylation, and strongly promote transcription from similar hypoxia response elements (HREs). However, there is increasing evidence for the functional non-equivalence of HIF-1a and HIF-2a, and in cancer, several recent studies have indicated that, at least in certain settings, they have contrasting effects on tumour growth (Maranchie et al, 2002;Kondo et al, 2002Kondo et al, , 2003Zimmer et al, 2004;Covello et al, 2005;Raval et al, 2005). In VHL-defective renal carcinoma cells (RCC), inactivation of HIF-a proteolysis upregulates both HIF-1a and HIF-2a with global induction of HIF target gene expression (Maxwell et al, 1999), stimulating investigations of the role of the HIF pathway in tumour development (Maranchie et al, 2002;Kondo et al, 2002Kondo et al, , 2003Zimmer et al, 2004;Raval et al, 2005).…”
mentioning
confidence: 99%
“…However, evidence has recently accumulated that the role of HIFs in oncogenesis is more complicated and may depend on cell types and specific settings. One striking example is HIF-2a, the protein that is absolutely required for tumor formation of RCCs with the inactivation of VHL while it acts as a tumor suppressor in malignant gliomas (19,21,(32)(33)(34). Interestingly, the effect of HIF-1a and HIF-2a on certain target gene expression has been shown to differ completely between RCC cells and other types of cancer cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that HIF-2a -mediated inhibition of hTERT expression may directly or indirectly contribute to apoptosis occurring in HIF-2a -overexpressing glioma cells. On the other hand, RCC cells with VHL inactivation require HIF-2a for their oncogenesis (21,(32)(33)(34). Given an essential role for telomerase in cell immortalization and transformation (1, 2), it seems reasonable that HIF-2a induces rather than inhibits hTERT expression in RCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation